Monitoring Reversible Tight Junction Modulation with a Current‐Driven Organic Electrochemical Transistor. Issue 5 (9th April 2021) - Lieberth, Katharina; Brückner, Maximilian; Torricelli, Fabrizio; Mailänder, Volker; Gkoupidenis, Paschalis; Blom, Paul W. M.
Abstract: The barrier functionality of a cell layer regulates the passage of nutrients into the blood. Modulating the barrier functionality by external chemical agents like poly‐l ‐lysine (PLL) is crucial for drug delivery. The ability of a cell layer to impede the passage of ions through it and therefore to act as a barrier, can be assessed electrically by measuring the resistance across the cell layer. Here, an organic electrochemical transistor (OECT) is used in a current‐driven configuration for the evaluation of reversible modulation of tight junctions in Caco‐2 cells over time. Exposure to low and medium concentrations of PLL initiates reversible modulation, whereas a too high concentration induces an irreversible barrier disruption due to nonfunctional tight junction proteins. The results demonstrate the suitability of OECTs to in situ monitor temporal barrier modulation and recovery, which can offer valuable information for drug delivery applications. Abstract : Reversible tight junction modulation of epithelial barrier tissue can be monitored in situ with the organic electrochemical transistor (OECT) in a current‐driven configuration. This method demonstrates the suitability of current‐driven OECTs to assess the temporal loss of barrier property as a function of tight junction modulator concentration operating as an impedance sensor with enhanced sensitivity.